Characterisation of a subgenomic molecule associated with South African cassava mosaic virus - Abraham, Natasha (My University, 2013)
Cassava (Manihot esculenta) is a major food crop in sub-Saharan Africa, where cassava is mostly used as a subsistence crop. In southern Africa, cassava production is affected by cassava mosaic disease (CMD). The impact of CMD on cassava yield has a devastating impact on the economy in southern Africa as it is also an important industrial crop. South African cassava mosaic virus (SACMV) is a distinct geminivirus known to cause CMD in Southern Africa. SACMV is a bipartite virus where the two components DNA-A (2800bp) and DNA-B (2760bp) code for important proteins needed for viral replication, movement and transmission. Defective interfering molecules are a type of subgenomic molecule associated with geminiviruses. DIs are dependent on the helper virus for replication. DIs are known to lead to symptom amelioration in plants infected with its cognate helper virus as a result of interfering with the helper virus replication in the plants. It is believed that they interfere with the replication, by competing for limited host and viral factors needed for replication by the helper virus. They also have a size-advantage to be selected over the helper virus, allowing for increased DI proliferation. A putative defective interfering (DI) molecule, isolated from a naturally infected field cassava, has been associated with SACMV. This DI molecule is derived from the DNA-B component of SACMV and is 1389bp in size, approximately half the size of DNA-B. In this study, the objectives were to investigate the effect of DI on SACMV replication and symptom development in a model host – N. benthamiana and cassava, the natural host of SACMV, in order to determine whether the DI was indeed an interfering molecule. Viral load (DNA-A and DNA-B) were determined using quantitative real-time PCR, and symptoms were scored according to a symptom severity index (1-5). The results from this study show that the DI did influence viral titres in N. benthamiana and cassava when infected with SACMV. However, the impact of DI on reducing viral replication and symptom attenuation was different in the two plant systems. In cassava, the symptom attenuation was more pronounced compared with N. benthamiana, which correlates to the respective viral titres, thus highlighting the differences in viral-host factor interactions during viral replication between a model host (Nicotiana benthamiana) and a natural host (cassava). It was also observed that the DI had an impact on viral replication and symptom attenuation, when it was present with SACMV- from onset of infection, but titres of DNA A and DNA B showed a cyclic pattern of increases and decreases during the infection process. A surprising observation made from this study was that either the presence of DI or reduced titres of DNA-B, due to interference by the DI, had a direct effect on the ability of the helper virus SACMV to develop a specific chlorotic symptom phenotype in infected leaves, suggesting that DNA B plays an important role in symptom development. Additionally, transgenic N. benthamiana transformed with a DI insert, which only replicates in the presence of the SACMV, was tested as a resistance strategy. Again, quantitative realtime PCR was used to determine viral load and symptoms were scored according to the symptom severity index. Unexpectedly, ours results showed that neither decreased viral load nor attenuated symptoms were observed when transgenic N. benthamiana was infected with SAMV, deeming the use of DI as a transgenic resistance approach non-viable. This suggests that although DI does decrease viral titres and lead to symptom attenuation during natural systemic infections or experimental inoculations, these DIs don’t hold potential in combating SACMV and CMD in a transgenic system.
Keywords: Mosaic diseases - South Africa.; Plant viruses - South Africa.